Increased pain unpleasantness and pain-related fMRI activation in the periaqueductal gray in Alzheimer's disease - Anderson, Alison R.; Monroe, Todd B.; Dietrich, Mary S.; Bruehl, Stephen P.; Iversen, W. Larkin; Cowan, Ronald L.; Failla, Michelle D. (Frontiers in Pain Research, 2022)
Background: Pain continues to be underrecognized and undertreated in people with Alzheimer’s disease (AD). The periaqueductal gray (PAG) is essential to pain processing and modulation yet is damaged by AD. While evidence exists of altered neural processing of pain in AD, there has not been a focused investigation of the PAG during pain in people with AD. Purpose: To investigate the role of the PAG in sensory and affective pain processing for people living with AD. Methods: Participants from a larger study completed pain psychophysics assessments and then a perceptually-matched heat pain task (warmth, mild, and moderate pain) during a functional MRI scan. In this cross-sectional study, we examined blood oxygenation level-dependent (BOLD) responses in the PAG and other pain-related regions in participants with AD (n=18) and cognitively intact older adults (age- and sex-matched, n=18). Associations of BOLD percent signal change and psychophysics were also examined. Results: There were significant main effects of AD status on the temperature needed to reach each perception of warmth or pain, where people with AD reached higher temperatures. Furthermore, participants with AD rated mild and moderate pain as more unpleasant than controls. PAG BOLD activation was greater in AD relative to controls during warmth and mild pain percepts. No significant differences were found for moderate pain or in other regions of interest. Greater PAG activation during mild pain was associated with higher affective/unpleasantness ratings of mild pain in participants with AD but not in controls. Conclusion: Results suggest a role for the PAG in altered pain responses in people with AD. The PAG is the primary source of endogenous opioid pain inhibition in the neuroaxis, thus, altered PAG function in AD suggests possible changes in descending pain inhibitory circuits. People with AD may have a greater risk of suffering from pain compared to cognitively intact older adults.